2006
DOI: 10.1080/08860220500461252
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Six Patients with Neuroleptic Malignant Syndrome Associated with Myoglobulinemic Acute Renal Failure

Abstract: Neuroleptic malignant syndrome is a rare but potentially lethal, rare reaction to neuroleptics which is characterized by altered levels of consciousness, extrapyramidal effects, autonomic instability, hyperthermia, and elevated serum creatine phosphokinase levels. The most serious complication of neuroleptic malignant syndrome is acute renal failure. We investigated six cases of neuroleptic malignant syndrome associated with myoglobulinemic acute renal failure due to rhabdomyolysis and effect of hemodialysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Melli et al demonstrated acute renal failure in 34 % of patients with rhabdomyolysis caused by NMS [8] and the serum creatinine level correlated positively with CPK in a linear fashion (R 2 = 0.12; p < 0.0001) [8]. In Japan, Sanai et al published a case series of six patients with rhabdomyolysis that caused myoglobinuria and AKI and they were treated successfully with hemodialysis and dantrolene [19]. In our study, 17.7 % patients had AKI that increased the odds of death by 2.3 times.…”
Section: Discussionmentioning
confidence: 97%
“…Melli et al demonstrated acute renal failure in 34 % of patients with rhabdomyolysis caused by NMS [8] and the serum creatinine level correlated positively with CPK in a linear fashion (R 2 = 0.12; p < 0.0001) [8]. In Japan, Sanai et al published a case series of six patients with rhabdomyolysis that caused myoglobinuria and AKI and they were treated successfully with hemodialysis and dantrolene [19]. In our study, 17.7 % patients had AKI that increased the odds of death by 2.3 times.…”
Section: Discussionmentioning
confidence: 97%
“…Sanai et al reported that acute renal failure induced from rhabdomyolysis developed in patients who had previously received haloperidol. [27] Since the recent development of stereological quantification methods, a large amount of numerical data has been readily obtained. [28,29] In the histological step of our study, dilatation of glomerular capillaries and large blood vessels was seen.…”
Section: Discussionmentioning
confidence: 99%
“…NMS is characterised by altered levels of consciousness, extrapyramidal effects (rigidity and akinesia), autonomic instability, hyperthermia, sweating and tremors or rigors 7476. Muscle rigidity is the cardinal feature of NMS and is often associated with myonecrosis, myoglobinuria, and elevated serum creatinine phosphokinase (CPK) levels 77.…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 99%
“…This, combined with rhabdomyolysis, can lead to acute renal failure, one of the more serious complication of NMS 74. Death has been reported to occur in 20–40% of cases 75 80 81…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 99%